Evaluation of Online Learning During the Covid-19 Pandemic on Universitas Negeri Padang - Dewi Sismira Yumiarti; Ambiyar Ambiyar (STAI Miftahul Ula Nganjuk, 2020)
This study aims to find out the learning process during the covid-19 pandemic on the campus of Padang State University. This research is an evaluation research. In this case, researchers evaluated online learning during the covid-19 pandemic at UNP campus using logic models (context, input, activities, output, outcome). The sample of this research is undergraduate students entering 2017 Faculty of Engineering Padang State University. Data collection techniques using questionnaires. The results showed that the implementation of online learning has been done well in the midst of the covid-19 pandemic, with the achievement of context components with good categories with TCR 80.87%, input components with sufficient categories with TCR 75.60%, process components with sufficient categories with TCR 75.50%, output components with good categories with TCR 82.60% and outcome components in sufficient categories with TCR 73.15%.